Synergistic Inhibition of Pro-Inflammatory Pathways by Ginger and Turmeric Extracts in RAW 264.7 Cells - Zhou, Xian; Münch, Gerald; Wohlmuth, Hans; Afzal, Sualiha; Kao, Ming-Hui (Tim); Al-Khazaleh, Ahmad; Low, Mitchell; Leach, David; Li, Chun Guang (Frontiers in Pharmacology, 2022)
Synergy plays a prominent role in herbal medicines to increase potency and widen the therapeutic windows. The mechanism of synergy in herbal medicines is often associated with multi-targeted behavior and complex signaling pathways which are challenging to elucidate. This study aims to investigate the synergistic mechanism of a combination (GT) of ginger (G) and turmeric (T) extracts by exploring the modulatory activity in lipopolysaccharides (LPS)-induced inflammatory pathways and key molecular targets. A Bioplex ProTM mouse cytokine 23-plex assay was utilized to assess the broad anti-cytokine activity of GT in LPS and interferon (IFN)-ɣ (both at 50 ng/mL)-activated RAW 264.7 cells. The inhibitory effects of individual and combined G and T on major proinflammatory mediators including nitric oxide (NO), tumor necrosis factor (TNF) and interleukin (IL)-6 were tested using Griess reagents and ELISA assays, respectively. Immunofluorescent staining and Western blot were used to investigate the modulatory effect of GT on key proteins in the LPS/TLR4 signaling transduction. The regulation of murine microRNA miR-155-5p was tested using real-time PCR. The IC50 value and combination index (CI) values were used to demonstrate potency and synergistic interaction, respectively. GT synergistically attenuated a range of pro-inflammatory mediators including inducible NO, major cytokines (TNF and IL-6) and secondary inflammatory cytokines (GM-CSF and MCP-1). GT significantly inhibited LPS-induced NF-kB p65 translocation, the activation of TLR4, TRAF6, and phosphorylation of JNK and c-JUN. Moreover, the suppressive effect of GT on each of the protein targets in this axis was stronger than that of the individual components. Real-time PCR analysis showed that GT suppressed miR-155-5p to a greater extent than G or T alone in LPS-stimulated cells. Our study demonstrates the synergistic mechanism of GT in downregulating LPS-induced proinflammatory pathways at the miRNA and protein levels. Our results establish a scientific basis for the combined application of G and T as an advanced therapeutic candidate in inflammatory diseases with broad and synergistic anti-inflammatory activity and multi-targeted mechanisms.